PENGEMBANGAN SISTEM INFORMASI JARINGAN BERBASIS ENTERPRISE RESOURCE PLANNING (ERP) PADA PT. SINAR ANTJOL - Bobby Bachry (IIB Darmajaya, 2013)
PT. Sinar Antjol is one of industries that contribute to the global industry. Including one of the private companies engaged in consumer goods in the Greater Jakarta area, and established in 1942 and consists of several branches and subsidiaries namely ORPA, LODAN, PLUIT, TANGERANG. Until now the administrative services is still manual, it can be seen when every administrative unit records every transaction in the computer with the spreadsheet program. In this thesis, the writer developed an administrative service system which is computerized, data related and all computers connected in the same network, thus, the administration service can run well and smooth. This research method began by analyzing the manual and not centralized system in the company then making the network system, network requirements specification, software requirement specification enterprise resource planning (ERP), Domain Servers, and Terminal Server. In the new administrative service system, using the LAN and WAN networking technology, PT. Sinar Antjol can serve both distribution and retailing quickly and accurately. Note: